Assessment of compatibilization efficiency of SEBS in the PP/PS blend. Issue 18 (22nd January 2018) - Zhao, Xueyan; Huang, Yajiang; Kong, Miqiu; Yang, Qi; Li, Guangxian
ABSTRACT: The compatibilization efficiency of styrene–ethylene/butylene–styrene (SEBS) triblock copolymer in immiscible polypropylene (PP)/polystyrene (PS) 20/80 blends was evaluated in terms of not only morphology, but also rheology and fractionated crystallization behavior. Besides varying SEBS loading, four different mixing protocols were used to vary SEBS dispersion state. PP 2 /PS/SEBS blend, prepared by two‐step method mixing PS and SEBS primarily, presents the largest droplet size (1.278 μm) at the critical compatibilizer concentration (CCC = 1 wt %). However, the CCC of blends prepared by the other protocols is 2 wt %. And at the CCC, PP/PS 2 /SEBS (two step method mixing PP and SEBS primarily) shows the smallest droplet size (0.908 μm), followed by PP/PS/SEBS (one step method). The rheology and crystallization behavior of PP/PS blends could also be utilized to assess the compatibilization efficiency of SEBS, but only in the case of mixing under the same protocol and the content of SEBS below a CCC. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46244. Abstract :